Access to Primary Education By Children With Physical Disabilities in Bwambara Sub-County Rukungiri District. - Akatukunda, Faith (Kabale University, 2024)
The purpose of the study was to investigate the factors influencing access to primary education by children with physical disabilities in the Bwambara sub-county Rukungiri District. The specific objectives of the study were; To find out how are children with physical disabilities admitted to primary schools in Bwambara Sub-County, How accessible are primary schools to children with physical disabilities and how affordable are primary schools in Bwambara sub-county to children with physical disabilities. The study used a qualitative research design and it employed a snowball sampling technique. A total of 8 children with physical disabilities were involved in the study and an interview guide was employed to collect information from respondents. The findings revealed that; CWPD are admitted to the school by picking an application form by their parents/guardian, filling it and then taken back to school, first denied admission and given after negotiation, denied admission in some schools and then opt to study in other school where they were offered admission and some CWPD pay extra amount of money to be admitted in the schools. The study further revealed; that some school buildings are not user-friendly to CWPD, their homes are located far away from where they study, unmodified transport routes are characterized by potholes, making it difficult to cross wheelchair users, the toilets are not user-friendly to CWPD since they share toilets with children without disabilities. The study findings indicated that the schools including state-owned charge a lot of money that children with physical disabilities from poor families cannot afford, that private schools charge an extra amount of money to CWD for purposes of meeting their disability and educational needs, some CWPD are offered full scholarship where they don't pay school fees and parents are capable to support CWPD at school. The recommendations that came out of the study were that schools should give admission to CWPD at a free cost, and Schools should put up a special desk for CWD so that when they come for admission they don't wait for long hours. School buildings should be modified through the construction of ramps Door entrances of school buildings should be enlarged to enable even wheelchair users to access school buildings, Schools establish toilets specifically designed for CWPD. Transport routes should be modified with ramps and special pavements to enable wheelchair users to access the transport routes easily, Parents/guardians of CWPD should engage in economic activities to support the education of CWPD, and Schools especially government owned should not charge money to enable even children from poor families stay at school.